Legal Education Bullying at the KH. Ahmad Dahlan Sipirok Islamic Boarding School - Dedy Suhendra; Ihsan Siregar; Yuli Miladiyah Siregar; Elsa Nilami Siregar; Amal Makruf Harahap (Universitas Muhammadiyah Malang, 2025)
Bullying behavior is still a significant problem in Indonesia. Bullying is a negative behavior that causes someone to feel uncomfortable, hurt, and occurs repeatedly. Child protection is needed as a reference to reduce bullying among children. This is in accordance with Law Number 35 of 2004 concerning Child Protection. Bullying can happen anywhere, both in everyday environments, as well as in public schools and boarding schools. Therefore, it is considered necessary to provide counseling about the prohibition of bullying in Islamic boarding schools with the aim of making students understand the dangers and prohibitions of bullying. The method of implementing the activity is always in the form of lectures related to the prohibition of bullying, both from a positive legal perspective and an Islamic legal perspective. The results of the activity show that bullying is a prohibited act and is threatened with imprisonment in accordance with Article 80 (1) of Law Number: 35 of 2014 concerning Child Protection, and according to positive law, and Allah will give severe punishment to Muslims who hurt fellow Muslims, will be repaid with hellfire and other bad retribution according to Islamic law. The conclusion from implementing this activity is that students increasingly understand that bullying is an act that is prohibited according to positive law and Islamic law because it can cause trauma which can have a negative impact on the psychology of the victim of bullying, and can even lead to the loss of the victim's life.